Excited‐State Dynamics of All‐trans‐Retinal Investigated by Time‐resolved Electronic and Vibrational Spectroscopy#. (26th February 2015) - Jen, Myungsam; Lee, Sebok; Pang, Yoonsoo
<x xml:space="preserve">Abstract</x> Time‐resolved electronic and vibrational spectroscopy has been applied to understand ultrafast excited state dynamics of all‐trans‐retinal. Femtosecond transient absorption spectroscopy provides an overview of the excited‐state dynamics of all‐trans‐retinal, and femtosecond‐stimulated Raman and infrared absorption measurements, which have not been reported previously, provide further details of the structural changes in the excited states. Three singlet excited states and one triplet excited state have been identified from these experimental results, which are in good agreement with many previous reports. A change in the energy order of the singlet excited state of all‐trans‐retinal between in polar and nonpolar solvents abruptly modifies the excited state dynamics. The intersystem crossing to the T1 state from the S1 state (nπ*) almost disappears in polar solvents, whereas the fluorescence from S3 and S2 states (ππ*) is almost absent in nonpolar solvents.